Tối ưu quá trình lên men thu nhận amino acid 1-lysine từ vi khuẩn Corynebacterium glutamicum VTCC-B-656 - Tâm, Trần Thị Minh; Hương, Nguyễn Thúy (VNU Journal of Science: Natural Sciences and Technology, 2009)
Abstract